MODERN EPIDEMIOLOGICAL AND ECONOMIC CHARACTERISTICS OF WHOOPING COUGH IN MOSCOW - I. V. Mikheeva; N. N. Fomkina; M. A. Mikheeva (Журнал инфектологии, 2019)
The goal of the study was the identification of epidemiological features of whooping cough and assessment of economic losses due to this disease in Moscow.Materials and methods. The retrospective descriptive epidemiological research is conducted. The statistical data on incidence of whooping cough in the Russian Federation and in Moscow from 2009 to June, 2018, the reports on registration of whooping cough cases as well as the results of laboratory testing on whooping cough in Moscow in 2017 have been studied. The general losses from whooping cough in Moscow in 2017 have been calculated.Results. The whooping cough incidence in Moscow considerably influences a situation on this infection in the country in general as more than 20% of all cases of whooping cough in Russia are registered in the capital, where the incidence exceed by 1.5–2.5 times the average country level. The incidence of whooping cough among children of 7–14 years and the share of this group of population in the structure of the whooping cough cases have increased in Moscow, and outbreaks of pertussis at schools are observed. In Moscow the general losses due to whooping cough in children of 7–14 years in 2017 were estimated as 19.72 million rubles. High performance of vaccinal prevention of whooping cough is confirmed: in Moscow in 2017 the coefficient of epidemiological efficiency of vaccination among children of 6-12 months was 97.7%, among children at the age of 1 year – 82.6%, 2 years -79.9%, 3 years – 74.9%. Weighted average of direct loss from a case of whooping cough was estimated as 31182.2 rubles. The general losses due to whooping cough in Moscow in 2017 were 67.88 million rubles.Conclusion. It is necessary to take additional measures for vaccinal prevention of whooping cough at children of school age and to support the high level of coverage by timely immunization of children of the first year of life. For assessment of economic feasibility of vaccinal prevention of whooping cough it is necessary to consider the size of economic losses due to this disease.